Prospective study on sterilization of rigid endoscopes in various otolaryngology clinics - Lakshmanan, Varun; M. K., Goutham; Karnaker, Vimal; Aroor, Rajeshwari; Kamath P., Shrinath; Bhat, Vadish; Varghese, Irene Gee (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Rigid endoscopes have revolutionized the diagnosis and management of upper aerodigestive pathologies. Inadequate disinfection and sterilization techniques carry increased risk for cross infection. Hence, they require high level disinfection to effectively reduce the bacterial and fungal contamination of rigid endoscopes. The present study analyses the various techniques of sterilization practised in Mangaluru, Karnataka, at different Otorhinolaryngology clinics. Methods: This prospective descriptive study was done on 30 rigid endoscopes. Swabs were taken from the endoscopes and container, and send for detailed microbiological examination. The different methods practised at various centres were documented. Results: The various sterilization technique practised was predominantly cetrimide and chlorhexidine solution (savlon) wash, ETO and Formaldehyde. However, among all techniques the microbiological studies revealed no growth. Conclusions: Rigid endoscopes have emerged as the best diagnostic equipment for otorhinolaryngologists. With regard to high level disinfection and sterilization, the endoscope must undergo recommended techniques. In our study the most commonly used techniques was cetrimide and chlorhexidine solution wash and less commonly ETO and Formaldehyde. The use of standard sterilization technique and maintaining the rigid endoscopes in sterile storage container is the key to maintain an organism free environment. The standard technique of prewash with water and soap water, then washing with cetrimide and chlorhexidine solution, then store the endoscope in sterile container is our recommendation.